Estimating inherent deformation in thin-plate Al-alloy joint by means of inverse analysis with the help of cutting technique. (September 2016) - Liang, Wei; Murakawa, Hidekazu; Deng, Dean
Highlights: A new method was developed to estimate inherent deformations in thin-plate Al-alloy joint. The proposed method is an effective tool to estimate inherent deformations for thin-plate joints with buckling distortion. The characteristics of inherent deformations in Al-alloy thin-plate joint were clarified by T-E-P FEM. Abstract: The elastic finite element method based on inherent strain theory has been recognized as an effective tool to estimate the total welding deformation for large and complex welded structures. When this computational approach is employed to predict welding deformation in a weldment, one prerequisite is that the inherent deformations of each welded joint included in the welded structure should be known beforehand. The inverse analysis method based on the combination of measuring technology and finite element method can be used to obtain the inherent deformations for various welded joints. However, if buckling distortion occurs in a welded joint, it will be difficult for this method to accurately obtain the inherent deformations especially in thin-plate joints. To overcome this difficulty, an improved inverse analysis method with the help of cutting technique was developed in the current study. The effectiveness of the proposed method was demonstrated through obtaining the inherent deformations in an Al-alloy thin-plate joint with buckling distortion.